Hubungan Kualitas Pelayanan Home Care Dengan Tingkat Kepuasan Keluarga Pasien Di Wilayah Kerja Puskesmas Makassar - Asmiana Saputri Ilyas (Lembaga Pengembangan Kinerja Dosen, 2024)
Health service in home is one of the health service that do in the family’s home stay for improving and defending family’s health. Home care gives priority to the fulfilment of health service with organizing the health service that have a quality with out an affense of code of ethics and standard of the quality of medical care profession in home care service in Batua Public Health Center jobs area in Makassar City. This study was do it with using descriptif survey with cross sectional study appraoach with amount of sampels 76 people wiht total sampling method. The results of this study showed that raliable has a relation with patients family statisfaction with p (0,002) < (0,05), assurance has a relation with patients family statisfac- tion with p (0,000) < (0,05), tangible has a relation with patients family statisfaction with p (0,000) < (0,05), emphaty has a relation with patients family statisfaction with p (0,002) < (0,05), responsiviness has a relation with patients family statisfaction with p (0,003) < (0,05). According to the results, its can be con- cluded that reliable, assurance, tangible, emphaty and responsiviness in home care service have a relation with patients family statisfaction. Suggested to the home care service officer in Batua Public Health Center to promote more about hme care service and always stay defending the nersing care service now.